Destination risk perception, image and satisfaction: The moderating effects of public opinion climate of risk - Xie, Chaowu; Huang, Qian; Lin, Zhibin; Chen, Yanying (Journal of hospitality and tourism management, 2020)
There is scant knowledge about how public opinion climate of risk influences tourist behavior in times of a safety crisis at the destination. In this study, we examined the potential moderation effect of public opinion climate on the relationships between tourist risk perception, destination image, and tourist satisfaction. We further distinguished tourist pre-travel and post-travel risk perceptions and proposed a path model linking pre-travel risk's effect on tourist satisfaction with post-travel risk perception and destination image as the serial multiple mediators. Data were collected from an on-site survey of tourists who visited China's Xinjiang area. The results indicate public opinion climate has a significant moderation effect above and beyond the effects of both pre-travel and post-travel risk perceptions on destination image and tourist satisfaction.